Principal component analysis for identifying period of seasons in Indonesia - Dewi Galuh Condro Kirono (Indonesian Journal of Geography, 2004)
The seasonal variability of Indonesian rainfall is almost entirely controlled by the Asian monsoon and so displays two distinct seasons, i.e. wet and dry seasons with transition periods in between. The onset of the monsoon varies with places, therefore, when dealing with seasonal rainfall, different researchers/authors have different way referring to the seasons. Hence, one definition may not be appropriate for all places. This problem creates a necessity for identifying the period of the season so that it can be used for Indonesia as a whole.This paper examines the spatial variation of the seasons over the Indonesia region and demonstrates the application of Principal Component Analysis (PCA) to solve the above mentioned problem, namely to identify the period of the seasons in Indonesia as a unity. The analysis is performed using monthly rainfall data from 63 stations spread across the country covering the period of 1947 to 1999 (52 years).The results support the fact that the wet season onset starts early in the northwestern part of Sumatra and propagates eastward and southward. It is not surprising if the north-western part of the country experiences a longer wet season than the east-northern part does. It is also shown that PCA is a useful tool for identifying the period of the season in Indonesia. Through the analysis, it is found that there are three types of rainfalls which have important influence on the year to year variation of the annual rainfall, i.e: the wet season (December to March), the dry season (May to September), and the dry-to-wet transition (October to November).